2014
DOI: 10.5688/ajpe7810188
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Student Pharmacist-Delivered Asthma Education on Child and Caregiver Knowledge

Abstract: Objective. To evaluate the effectiveness of asthma education delivered by student pharmacists and to assess the impact of child and caregiver baseline asthma knowledge on asthma control in children. Design. Student pharmacists developed and implemented asthma self-management education interventions for children and their caregivers and performed asthma screenings for children at a series of asthma camps. Assessment. Eighty-seven children, ages 5-17 years, and their caregivers were enrolled in this study. A pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 15 publications
3
11
0
10
Order By: Relevance
“…Mean knowledge scores in the intervention group were significantly better than controls ( P < .05) at follow‐up in our study. This is similar to many earlier studies and provides further evidence to the fact that education about asthma improves knowledge about asthma 6,7,9,17,24 . In our study, both groups showed improvement in parental knowledge items related to chronicity, genetic disposition, asthma trigger by dust, asthma masquerade as chronic cough, use of inhalers for acute attack, and efficacy of long‐term inhalation.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Mean knowledge scores in the intervention group were significantly better than controls ( P < .05) at follow‐up in our study. This is similar to many earlier studies and provides further evidence to the fact that education about asthma improves knowledge about asthma 6,7,9,17,24 . In our study, both groups showed improvement in parental knowledge items related to chronicity, genetic disposition, asthma trigger by dust, asthma masquerade as chronic cough, use of inhalers for acute attack, and efficacy of long‐term inhalation.…”
Section: Discussionsupporting
confidence: 92%
“…Our study showed a significant improvement in parental knowledge and attitudes after the educational intervention; however, there were no differences in asthma severity and control. These results are comparable with other studies that showed improvement in knowledge, self‐efficacy, and attitudes after educational intervention; however, evidence regarding postintervention clinical outcomes has been conflicting 3,6‐9,16‐25 …”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Patient education in asthma self-management has emerged as a therapeutic intervention to help patients to manage and recognize asthma, and hopefully to become active, self-efficacious participants in their asthma care (Al-Atawi, 2017). Additionally Asthma selfmanagement education programs for children and adolescents leads to significant improvement in lung function, controlling the disease, reduce missed school days, reduces emergency department visits and hospital admissions (Elliott et al 2014). Compliance with therapeutic regimens in bronchial asthma, particularly in children, is low.…”
Section: Introductionmentioning
confidence: 99%
“…These findings, when taken together with existing research that identify parent/child knowledge gaps (23, 33) and research showing that clinicians and families think differently about asthma and asthma management, (24) highlight the potential for tailored education that addresses the knowledge deficits and education preferences of individual children and their caregivers. The inclusion of youth and caregiver specific interests and preferences will likely strengthen intervention successes.…”
Section: Discussionmentioning
confidence: 74%